SISTEM PENILAIAN PRESTASI KERJA PEGAWAI KOMISI PENYIARAN INDONESIA DAERAH ACEH - Said Firdaus (Jurnal Ilmiah Manajemen Muhammadiyah Aceh, 2011)
Aceh Indonesian Broadcasting Commision is an independent institution and has authority according to the law to manage the running of broadcasting in Aceh. In performing it tasks and function, KPID has been assisted by a secretariat where the personnels are outsourcing staff. To evaluate the performance of staff, KPID carried out performance evaluation system.Performance evaluation system at KPID is in form of individual evaluation where a superior directly evaluate behaviour and performance of his/her subordinates. For behaviour evaluation, the results of evaluation is in form of good, middle, and less good behaviour. While for performance, the results is in form of the achievement of job volume. The results would then be base for the decision of the institution.According to evaluation been done and compared with the theory, it can be concluded that in the staff job performance evaluation within KPID, the system used has been complied with the regulation. It can be seen from the administration of staff job performance evaluation at KPID where the method used was the same as the theory.Â